2020
DOI: 10.1002/msc.1499
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions on shared decision making during prescription of subcutaneous biological drug treatments for inflammatory arthritis: The RHEU‐LIFE survey

Abstract: Objectives: The aim of this study was to explore the preferences of patients with rheumatic diseases and their perceived experience regarding participation in shared decision making (SDM) when they were prescribed a subcutaneous (SC) biological drug. Methods: A printed survey was handed to 1,000 patients with inflammatory rheumatic diseases treated with SC biological drug. The survey included closed questions about preferences regarding decision making and about patients' experience when they were prescribed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Oral route of administration was preferred over parenteral one, with daily frequency partially counterbalancing such effect. In a Spanish study, about a third of RA patients reported willingness to enter the treatment decision process at the time of the choice of biological (b)DMARDs, in a so-called 'shared decision' approach, although the majority of patients delegated this decision to the rheumatologist (9). Nonetheless, how to operationalise shared decisions in inflammatory arthritis and whether such approach might be favourable in terms of disease outcome along with better care experience is still matter of debate.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral route of administration was preferred over parenteral one, with daily frequency partially counterbalancing such effect. In a Spanish study, about a third of RA patients reported willingness to enter the treatment decision process at the time of the choice of biological (b)DMARDs, in a so-called 'shared decision' approach, although the majority of patients delegated this decision to the rheumatologist (9). Nonetheless, how to operationalise shared decisions in inflammatory arthritis and whether such approach might be favourable in terms of disease outcome along with better care experience is still matter of debate.…”
Section: Reviewmentioning
confidence: 99%
“…• The most recent data regarding the global health of RA population indicate that, despite the extensive scientific knowledge on the treatment of RA, the translation of these into the community of patients with RA has not yet took place (2-5) . • The urgency of the emerging treatment of RA, rather than the availability of new drugs, appears to be to design and implement new treatment delivery strategies, with the involvement of patients to complete this process (6)(7)(8)(9)(10).…”
Section: Take Home Messages On Ra Population Healthmentioning
confidence: 99%